Costos del Proceso de Elaboración del Banano Confitado y su Relación con el Precio de Venta - Vera Vera, Verónica Vanessa (2018)
The following work is focused on the management of accounting information. The Company FUTURCORP S.A, is located at Km. 931 2 / via Pueblo Viejo - San Juan, its offices of the administrative part are in the City of Guayaquil, it is a company that is engaged in foreign trade with its tax identifier # 0991208844001 with type of contributor "SOCIEDADES", its social capital is constituted by the shareholders' meeting composed of two members of a single family with a contribution of 50% each. FUTURCORP S.A has the vision "To make quality a standard of living for the company". The Mission of FUTURCORP S.A "It was created for the elaboration of foods derived from natural fruits, which serve as raw material for the manufacture of food products marketing them under the philosophy of continuous improvement based on training, cutting-edge technology, quality in processes and products, application of appropriate systems of Quality assurance, maintenance of high quality and effective indexes application of environmental protection policies are the key factors of success